Penguatan Kapasitas Usaha Mikro Perempuan melalui Pendampingan Tata Kelola Keuangan dan Pemasaran Digital di Desa Senggreng, Kabupaten Malang - Adrian Hartanto Darma Sanputra; Eka Ananta Sidharta; Tatas Ridho Nugroho; Nasya Nur Afifa; Zikri Al Annas Wibisono; Cornelia Agatha (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2026)
Micro-enterprises run by members of the PKK group in Senggreng Village, Sumberpucung Sub-district, Malang Regency, face two related problems, namely weak production governance and low financial literacy combined with limited digital marketing. This community service activity aims to improve partner capacity in product standardization, financial recording, and digital marketing. The activity used participatory training and mentoring carried out in four stages, namely preparation, implementation, mentoring, and evaluation, with pre- and post-activity measurement of 30 participants. The results show an increase in product standardization understanding from 50% to 95%, financial literacy from 50% to 87%, and digital marketing from 50% to 88%. All participants kept regular cash books and opened digital business accounts, while 24 participants produced three or more promotional contents. Achievements in all three areas exceeded the 70% target. Combining product improvement, financial recording, and marketing in a single program produced more complete results than standalone training. The activity produced a training module, a packaging kit, and a brand identity for the partner.